Evaluating the Development Potentials of Agri Sites for Tourism: The Case of Tigaon, Province of Camarines Sur, Philippines (Global Journal of Management and Business Research, 2020)
The study aims to evaluate the potential and prospects of agritourism sites in Barangays Tinawagan and Libod, Tigaon, Camarines Sur through Community-Based Participatory Action Research approach. The result of the study will serve as baseline information to develop community-managed agritourism trek in the area to help the community uplift the socio-economic status. The study focuses on classifying the potential agritourism sites from the point of origin, accessibility, mode of transportation and side attractions, evaluating the environment and surroundings of the locality and other services.
Keywords: agritourism; development; tourism potentials; community based participatory action research